A paraungual tumor? - No, just tungiasis - Golouh, Rastko (Radiology and oncology (Ljubljana), 2000)
Background. Tunga penetrans is a burrowing flea that is prevalent in Central and South America, the Caribbean, tropical Africa, India and Pakistan. Tungiasis results from cutaneous infestation by gravid female flea, Tunga penetrans. Case report. We report a case of tungiasis in a male who had been on a tourist expedition to Bolivia and Peru. The condition had manifested as aparaungual infiltration of a toe, that was clinically suspicious for tumor. Conclusions. Microscopic examination of the lesion and travel history led to the diagnosis of tungiasis. This is the first case report of Tunga penetrans infestation in Slovenia.
Keywords: Dermatomycoses; Dermatophytes; Diagnosis; Fleas; koža; Middle age; South america; Toes; Travel; tungiaza; zajedalci